10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Violence against women is a preventable public health problem that causes harm in many ways. When experienced around the time of pregnancy, violence is an important contributor to pregnancy-associated morbidity and mortality in the United States. Survivors may experience extensive short- and long-term impacts on their physical health, mental health, and overall well-being. Violence victimization around the time of pregnancy can also lead to pregnancy complications and poor pregnancy outcomes. The harmful effects extend beyond the woman to her baby, other children in the home, additional family members, and her larger community. A comprehensive prevention approach is needed that includes collection of high-quality data to characterize the problem and inform prevention programs, primary prevention to stop violence before it begins, and effective trauma-informed programs, policies, and practices to respond effectively to violence when it happens and reduce further harm. This article summarizes the Centers for Disease Control and Prevention (CDC)'s work related to preventing violence affecting pregnant and postpartum women, aligning with the CDC priority to protect life and the family. We describe surveillance and programmatic activities across different organizational units at CDC, as well as gaps and opportunities to expand collaboration with the goal of improving health outcomes for women, infants, and families by preventing violence.